Hepatocyte growth factor and alternative splice variants - expression, regulation and implications in osteogenesis and bone health and repair. (1st September 2016) - Frisch, Rachel N.; Curtis, Kevin M.; Aenlle, Kristina K.; Howard, Guy A.
ABSTRACT: Introduction : Bone marrow-derived mesenchymal stem cells (MSCs) can differentiate into multiple cell types, including osteoblasts, chondrocytes, and adipocytes. These pluripotent cells secrete hepatocyte growth factor (HGF), which regulates cell growth, survival, motility, migration, mitogenesis and is important for tissue development/regeneration. HGF has four splice variants, NK1, NK2, NK3, and NK4 which have varying functions and affinities for the HGF receptor, cMET. HGF promotes osteoblastic differentiation of MSCs into bone forming cells, playing a role in bone development, health and repair. Areas Covered : This review will focus on the effects of HGF in osteogenesis, bone repair and bone health, including structural and functional insights into the role of HGF in the body. Expert Opinion : Approximately 6.2 million Americans experience a fracture annually, with 5-10% being mal- or non-union fractures. HGF is important in priming MSCs for osteogenic differentiation in vitro and is currently being studied to assess its role during bone repair in vivo . Due to the high turnover rate of systemic HGF, non-classic modes of HGF-treatment, including naked-plasmid HGF delivery and the use of HGF splice variants (NK1 & NK2) are being studied to find safe and efficacious treatments for bone disorders, such as mal- or non-union fractures.